2013
DOI: 10.3109/00016489.2013.857786
|View full text |Cite
|
Sign up to set email alerts
|

Minimally invasive transnasal medial maxillectomy for treatment of maxillary sinus and orbital pathologies

Abstract: The presented method allowed for good overall symptom control and eradication of disease confirmed endoscopically in about 90% of cases with an inflammatory type of disease. The visualized reach within the maxillary sinus with commercially available endoscopic instruments was conspicuously improved as compared with middle meatal antrostomy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 19 publications
0
7
0
1
Order By: Relevance
“…Bei anderen Varianten der medialen Maxillektomie wird der Ductus nasolacrimalis erhalten [293,296]. Der prälacrimale Zugang zur Kieferhöhle [297][298][299][300][301] Eine maximale Erweiterung der Kieferhöhlenfensterung über den mittleren Nasengang erfordert in den meisten Fällen die Eröffnung der Bulla ethmoidalis. Dies ist Teil der vorderen Siebbeinoperation.…”
Section: Mediale Maxillektomieunclassified
“…Bei anderen Varianten der medialen Maxillektomie wird der Ductus nasolacrimalis erhalten [293,296]. Der prälacrimale Zugang zur Kieferhöhle [297][298][299][300][301] Eine maximale Erweiterung der Kieferhöhlenfensterung über den mittleren Nasengang erfordert in den meisten Fällen die Eröffnung der Bulla ethmoidalis. Dies ist Teil der vorderen Siebbeinoperation.…”
Section: Mediale Maxillektomieunclassified
“…There were a total of 6 studies that met eligibility criteria and were included into the study (Figure 1). 5,7,[10][11][12][13] Across these studies, a total of 255 patients underwent expanded surgery with EMMM for chronic maxillary sinusitis, with follow-up ranging from 12 months to 82.8 months. Of the articles included in this review, 2 articles contained Level 2B evidence (well-designed cohort study), 5,7 and 4 contained Level 4 evidence (poorly designed cohort studies) based on Oxford Center for Evidence-based medicine Levels of Evidence.…”
Section: Included Studiesmentioning
confidence: 99%
“…Of the articles included in this review, 2 articles contained Level 2B evidence (well-designed cohort study), 5,7 and 4 contained Level 4 evidence (poorly designed cohort studies) based on Oxford Center for Evidence-based medicine Levels of Evidence. [10][11][12][13][14] One study reported entirely on cystic fibrosis (CF) patients with CRS, and the other 5 reported on non-CF CRS patients. 7 A summary of the included articles can be found in Tables 1 and 2.…”
Section: Included Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…The pre-lacrimal approach to the maxillary sinus [ 301 ], [ 302 ], [ 303 ], [ 304 ], [ 305 ] allows both, a complete overview of the whole maxillary sinus, including the pre-lacrimal recess and all other recesses (applying optics with angled views and also angled instruments) together with the preservation of the inferior turbinate and the nasolacrimal duct (Figure 2 (Fig. 2) ).…”
Section: Type and Technique Of Endonasal Sinus Surgerymentioning
confidence: 99%